PENGARUH PENAMBAHAN SUPLEMEN HERBAL PADA PAKAN TERHADAP DIFERENSIASI LEUKOSIT IKAN DAN SINTASAN IKAN PATIN (Pangasionodon hypopthalmus) - Ronal Kurniawan; Henny Syawal; Irwan Effendi (Universitas Sriwijaya, 2020)
The use of herbal supplements is an alternative to increase food security, because it can stimulate fish appetite and increase fish immunity against disease. The aims of this research to know the total leukocytes, leukocyte differentiation and survival rate of striped catfish fed with dosage fermented herbal supplements, and to obtain the best dosage. The implementation of research was from June until August 2019 at the Parasites and Fish Diseases Laboratory, Faculty of Fisheries and Marine, Riau University. The method used is a completely randomized design (CRD), with four treatments and three replications, namely P0 (without the addition of herbal supplements), P1 (herbal supplement dose 100 mL / kg of feed), P2 (200 mL / kg of feed), and P3 (300 mL / kg of feed). Maintenance of fish is carried out for 60 days, with a stocking density of 50 fish / m. The results showed that the herbal supplementation at a dose of 200 mL / kg of feed (P2) was the optimal dosage in stimulating total leukocytes and differentiation of catfish leukocytes. P2 treatment resulted in total leukocytes of 11.26 x 104 cells/mm3, further differentiation of leukocytes such as lymphocytes, monocytes, neutrophils and platelets of 81.67%, 6.33%, 5.67% and 6.33%. In addition it produces a survival rate of 100%. Key words : Fermented herbal supplement, striped catfish, total leukocytes